Application of audio magnetotelluric method in tunnel advanced detection—Taking Tianheshan tunnel of Hexing Railway as an Example - Zhao, Yuan-cheng (Applied geophysics, 2025)
The geological disasters such as collapse, mud bursting and water gushing often occur during tunnel construction. Thus, it is of great significance to detect the hidden geological disasters in front of the tunnel. The audio magnetotelluric (AMT) was applied for the advanced detectionstudy during the boring process of the Tianheshan tunnel in the Taihang Mountains. Three AMT profiles were deployed above the tunnel, and the data obtained in the field were analysed in terms of electrical principal axes. From shallow to deep, the direction of the geoelectric strike angle changes, generally between 30° and 60° NE, which is consistent with similar to the direction of the Taihangshan Uplift, and the data show some 3D characteristics. Two-dimensional(2D) and three-dimensional(3D) inversion methods were adopted to jointly study the subsurface structural information, and the resistivity model was geophysically and geologically interpreted. Two sets of low resistance anomalies were found, and it was hypothesised that the near-erect low-resistivity anomalies in the east might be a fragmentation zone, while the low resistance anomalies in the west, which are inclined to the westward, might be a tectonic structure or fragmentation zone related to the regional major fault, and the results of the tunnelling confirmed the reliability of the inversion interpretation. The 3D inversion can fully reflect the development scale and morphological changes of the fracture zone, and the inversion model is more reliable. Finally, it is concluded that the audio magnetotelluric method, which adopts advanced acquisition, processing and inversion interpretation techniques, is an effective means of over-detection of tunnels.